Global metabolome changes induced by environmentally relevant conditions in a marine-sourced Penicillium restrictum - Le, Van-Tuyen; Bertrand, Samuel; Brandolini-Bunlon, Marion; Gentil, Emmanuel; Robiou du Pont, Thibaut; Rabesaotra, Vony; Wielgosz-Collin, Gaëtane; Mossion, Aurélie; Grovel, Olivier (Comptes Rendus. Chimie)
Marine fungi have been found in all habitats and are able to adapt to their environmental niche conditions. In this study, a combination of liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) and gas chromatography coupled to mass spectrometry (GC-MS) analytical approaches was used to analyse the metabolic changes of a marine-sourced Penicillium restrictum strain isolated from a marine shellfish area. The P. restrictum MMS417 strain was grown on seven different media including an ecological one with two different water sources (synthetic seawater and distilled water), conditions following the One-Strain-Many-Compounds (OSMAC) approach. Extracts of all media were analysed by LC-HRMS (lipids and specialised metabolites profiling) and GC-MS (fatty acids profiling). Acquired data were analysed using a multiblock strategy to highlight metabolic modification in regard to water conditions and to environmentally relevant conditions (mussel-based culture medium). This revealed that fatty acid composition of lipids was the most altered part of the explored metabolisms whether looking to the effect of water or of environmentally relevant conditions. In particular, data showed that P. restrictum MMS417 is able to produce lipids that include fatty acids usually produced by the mussel itself. This study also provides insight into the P. restrictum adaptation to marine salinity through fatty acids alteration and shows that lipid metabolism is far more altered in an OSMAC approach than the specialized metabolism. This study finally highlights the need for using environment-mimicking culture conditions to reveal the metabolic potentialities of marine microbes.